Corrosion Inhibition of Carbon Steel under Two Phase Flow (Water-Petroleum) Simulated by Turbulently Agitated System - J. M. Slaiman, Qasim; O. Hasan, Basim; A. Mahmood, Hussein (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The corrosion of carbon steel in single phase (water with 0.1N NaCl ) and two immiscible phases (kerosene-water) using turbulently agitated system is investigated. The experiments are carried out for Reynolds number (Re) range of 38000 to 95000 corresponding to rotational velocities from 600 to 1400 rpm using circular disk turbine agitator at 40 0C. In two-phase system test runs are carried out in aqueous phase (water) concentrations of 1 % vol., 5 % vol., 8% vol., and 16% vol. mixed with kerosene at various Re. The effect of Reynolds number (Re), percent of dispersed phase, dispersed drops diameter, and number of drops per unit volume on the corrosion rate is investigated and discussed. Test runs are carried out using two types of inhibitors: sodium nitrite of concentrations 20, 40, and 60 ppm and sodium hexapolyphosphate of concentrations 485, 970, and 1940 ppm in a solution containing 8 % vol. aqueous phase (water) mixed with kerosene (continuous phase) at 40 °C for the whole range of Re. It was found that increasing Re increases the corrosion rate and the presence of water enhances the corrosion rate by increasing the solution electrical conductivity. For two phase solution containing 8% vol. and 16% vol. of water the corrosion rate was higher than single phase (100 % vol. water). The main parameters that play the major role in determining the corrosion rate in two phase were concentration of oxygen, solution electrical conductivity, and the interfacial area between the two phases (dispersed and continuous). Sodium nitrite and sodium hexapolyphosphate were found to be efficient inhibitors in two phase solutionfor the investigated range of Re.